Isolation and identification of dermatophytes fungi from under two year children in diaber location - kadhim, Majid; hussainy, Abbas al. (Al-Qadisiyah Journal of Pure Science, 2017)
This study has been done to insulate and diagnose the( Candida spp ) from babies under two years in the place of the baby nappy . To know exactly the existence attribution of these (Candida spp ) and to study their sensivitiy t o anti-funguses (Ltraconazol (LTZ ) , Fluconazole (FLZ ) , Amphtericin – B , Nystatin , Ketoconazol (KTZ) ) . This study has also included discerning the relasionship between the way of using the baby nappy and the possibility of being ill by dividing it into three patterns ( neutral , intermitted and nightly ) . On the other side , discerning the effect of the environmental factor represented by the baby habitation whether it is city or countryside .Then , the Uresis test has been used to separate it from the continents while the germ tube test is used to differ the white ovaries from others . The use of to prevent the growth of the contaminant bacteria and the diagnose of different kinds is depended upon the the instruments of testing (RapiD , Yeast, plus ,, Color , Guide ) . The results were analysied by using a statistical programme ( SPSS) 2007 in analyzing the data to study the effect of different factors to the tested features . The (ANOVA ) was used on (10,0 ) incorporeal level by the statistical programme ( Excel ) . When the incorporeal differences were compared with the averages by ( LSD) the results were that the tested anti-funguses had a fatal effect towards the all kinds of isolated yeasts in different degrees depending on the kind of yeasts . And it demonstrated a clear impact to the way of using the baby nappy and the habitation of the patient.